Sex Differences in Migraine: A Twin Study - Fitzgerald, Morgan C.; Saelzler, Ursula G.; Panizzon, Matthew S. (Frontiers in Pain Research, 2021)
Migraine is a neurological disorder with a prominent sex-difference such that two thirds of sufferers are female. The mechanisms behind the preponderance of migraine in women have yet to be elucidated. With data on 51,872 participants from the Swedish Twin Registry, we report results from two distinct analyses intended to clarify the degree to which genetic and environmental factors contribute to sex differences in migraine. First, employing data from same-sex monozygotic and dizygotic twins, as well as opposite-sex dizygotic twins, we fit a sex-limitation model to determine if qualitative genetic differences (i.e., are different genes involved) and/or quantitative genetic differences (i.e., is a phenotype equally heritable across men and women) were present between men and women. Next, we compared the prevalence of migraine in individuals from opposite-sex and same-sex twin pairs to determine whether differences in the prenatal hormonal environment contribute to migraine risk. In the final analytic sample, women were found to have a significantly higher rate of migraine without aura relative to men (17.6% vs 5.5%). In the first analysis estimating additive and non-additive genetic influences, tests of qualitative and quantitative sex differences resulted in non-significant changes in model fit. This indicates equivalent latent genetic factors contribute to migraine heritability and risk across the sexes. The broad-sense heritability for migraine in men and women was found to be .45 (95% CI = .40-.50). However, a simplified genetic model, one that estimated only additive genetic influences, provided subtle evidence for different genetic effects between men and women, while heritability estimates remained equal. In the analysis of opposite-sex twin pairs, we observed a significant increase in migraine risk for females with a male co-twin relative to females with a female co-twin (OR = 1.51, 95% CI = 1.26 – 1.81). Results suggest that prenatal factors may contribute to the differential risk of migraine across men and women.